Aquinas at 800 - Papers from the 2024 Notre Dame Conference: Integrating the Various Human Dimensions into the Vision of God in Heaven - Vial, Catalina (European journal for the study of Thomas Aquinas, 2025)
The beatific vision of God in heaven is at the heart of the Christian faith. Thomas Aquinas affirms that the principal faculty of the human person is the intellect, and that the vision of God will consist primarily in an intellectual operation. The emphasis that Aquinas places on the operation of the intellect could lead one to think that it is an overly intellectualistic conception of what our happiness in heaven will be. On the other hand, contemporary authors such as Hans Boersma point out that in the Thomistic doctrine of the beatific vision the corporeal dimension of the human person is of little relevance. The purpose of this article is to explain how the different dimensions of the human person -intellect, will and corporeality- are integrated in the vision of God in heaven according to Thomistic doctrine.